Bitcoin mining, the way to process transaction information or the way to make money? - Jiangdong Cao; Wei Cao (Universitas Lampung, 2019)
Bitcoin is a crypto currency introduced by Satoshi Nakamoto in 2008. It has the features of decentralization cross-border and fixed total amount and has become one of the most widely used crypto-currencies. Bitcoin, as a new digital currency system, innovatively makes the use of cryptographic elements and consensus mechanisms and builds up a secure decentralized system. The Blockchain, as the core of Bitcoin, uses peer-to-peer network communications and backs up transaction data in every node of the system, thus creating a huge distributed public book. It is essentially a decentralized distributed ledger database, and the decentralization means that the transaction is broadcast to the entire network, where everyone is involved in book keeping. In order to make every participant in the Blockchain willing to participate in the bookkeeping, the reward mechanism of the Bitcoin system is mining. This article first introduces the concept of Blockchain technology, then expounds the principle and the operation mechanism of the Bitcoin and the Bitcoin mining principle, introduces an example of Bitcoin mining in-depth study and analysis, finally, summarize and prospect the development of the Bitcoin mining.